Moment of Truth: Springfield Textiles - Kumar , Prem; Aneet , (Gyan Management Journal, 2009)
Mr Sarkar, Chairman and Managing Director, Springfield Textiles looked at the contents of the Business Review. An article on Moments of Truth caught his attention. The article was written by a management expert describing how critical events change the history of individuals and organizations. Mr Sarkar read the paper with great deal of curiosity. After finishing the paper, he closed the journal an d asked th e driver to drive at a steady speed without causing much jerks. He closed his eyes and put his head on the headrest in his Mercedes car. "T he Sptingfield Group has come a lo ng way in the last forty years", he thought. Th e ev ents started running like a film in his mind .Mr P. Sarkar, a Po st- gra d uate in Business Studies from a leading B-Schoot-was Ch ai rm an of th e largest Te xtiles conglomerate in India. He was a precocious child of a leading businessman at a growing town in North India. His father established a co tton yarn spinning facto ry- the Sp ringfield Textiles in 1962. The plant started production in 1965. Mr Sarkar joined the family business much against his wishes in 1966. He was more in terested in te aching and rese arch but gave in to the demands of the family business.
Keywords: Springfield Textiles; Moments; businessman; North India